Perancangan Aplikasi Latihan Pemahaman Materi Bahasa Baku dan Non Baku Menggunakan Metode Scoring System Berbasis Android - Lubis, Baktiar (TIN: Terapan Informatika Nusantara, 2020)
Nowadays, computer skills can be used in various fields to teach, provide information, and provide entertainment. Computers can also be used to assist in the teaching and learning process. To facilitate the delivery of material, it can be packaged attractively in the form of an Android-based application, which is educational and entertaining for students. The topic of this discussion is the design of an application to understand standard and non-standard language material comprehension exercises using the Android-based scoring system method. Where to use this application can help students in learning standard and non-standard language material that is computerized. Therefore, the authors apply the scoring system method to determine scores and categories in the assessment of standard and non-standard language material, there are three categories, namely unfavorable, good and very good. The purpose of this study was to design an Android-based application of standard and non-standard language materials, where the training score implementation used the scoring system method. This application will make it easier for students to learn standard and non-standard languages, because the application system is already in the form of android so that it adds attractiveness to students.